Application Géomatique Pour La Cartographie De La Vulnérabilité Environnementale Engendrée Par Les Déchets Miniers De La Mine Ferrifere De Nador (Nord-est du Maroc) - Lakrim, Mohamed; Mesrar, Laila; El Aroussi, Omar; Jabrane, Raouf (European Scientific Journal, ESJ, 2016)
The field work has been done to study the impact of acid mine drainage on the environment. Space pollution measurement was carried out on the basis of interesting physicochemical and geomatic analyses of water and solid region outcrops. The study showed that the phenomenon under study represents an alarming problem that is attributed to the presence of huge stocks of mining waste sulphur, directly exposed to a Mediterranean climate and thus remains capable of accelerating the oxidation process. The classification of zones according to the levels of fragility is entailed by the necessity to opt for a model that is compatible with different intrinsic and extrinsic parameters. The study was concluded by the superposition of six thematic layers charting the environmental vulnerability map by the GIS. The findings demonstrated that most vulnerable zones near the points of exploitation are very oxidized in bottomlands or in places well apart from carbonate facies (pH <3.